Exploring Students’ Perception in Teaching Tenses Through Poem in English Literature Students of Pamulang University - Rosyidah, Rossy Halimatun; Meylinda, Linda (Program Studi Magister Pendidikan Bahasa dan Sastra Indonesia, Program Pascasarjana, Universitas Pasundan Bandung, 2023)
This research aims to investigate students' perceptions of learning tenses through the use of poetry and its effectiveness among students majoring in English literature at Pamulang University. Data was collected through analysis of responses from 30 students in the third semester using a questionnaire. Data analysis was used reduction of the data, display the data, and drawing conclusion and verification. The results of the analysis show positive student responses to this learning method, with the majority of students finding it to be an interesting and rewarding experience, the use of poetry in teaching tenses increases understanding of grammatical concepts, increases students' learning motivation, and strengthens their understanding of the everyday context of the tenses being taught. Thus, this research supports the use of poetry as an effective learning tool in improving English grammar learning at university level